2010
DOI: 10.1002/cncr.24791
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose radioimmunotherapy combined with extracorporeal depletion in a syngeneic rat tumor model

Abstract: BACKGROUND:The aim of the current study was to investigate the possibility of increasing the maximal tolerated dose (MTD) of a tumor-selective radiolabeled antibody when radioimmunotherapy (RIT) is combined with extracorporeal depletion of radioimmunoconjugates from the circulation. Furthermore, the authors evaluated whether this increase in dose improved the therapeutic effect on solid manifest tumors in an immunocompetent animal model. METHODS: Rats were injected with high activities/body weight of lutetium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…12 Må rtensson et al showed that treatment with the MTD resulted in CR in all animals, although metastases were found in 3 of 6 rats. This indicated the need for maintenance treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Må rtensson et al showed that treatment with the MTD resulted in CR in all animals, although metastases were found in 3 of 6 rats. This indicated the need for maintenance treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] In an effort to improve RIT, we have used a syngeneic rat colon carcinoma model utilizing the cell line BN7005, in which a complete response (CR) of inoculated tumors was achieved after a single administration of RIT consisting of 177 Lu-labeled mAbs, but with the development of distant metastases in about half of the animals after the treatment. 12 In the present study, we evaluate whether consolidation therapy with unlabeled antibodies after RIT enhances the therapeutic effect and/or delays the clinical symptoms of metastatic disease. The choice of unlabeled antibodies for consolidation therapy is based on the well-established therapeutic effects of various unlabeled antibodies in clinical cancer care.…”
mentioning
confidence: 99%
“…[76][77][78][79][80][81] In a series of studies, Tennvall et al have demonstrated the utility of extracorporeal affinity adsorption using avidin columns to deplete biotinylated radiolabeled antibodies from circulation. [82][83][84][85][86][87][88][89][90][91][92] In one of the earliest demonstrations of the approach using athymic rats bearing human melanoma and lung cancer xenografts, removal of biotinylated 125 I-labeled antimelanoma (MAb 96.5) and anticarcinoma (MAb L6) antibodies improved the tumor to normal tissue ratios by a factor of four or five. 91 Subsequent studies using a syngeneic model of colorectal cancer in rats with chimeric anti-Lewis Y antibody BR96 demonstrated the benefits of immunoadsorption from the whole blood.…”
mentioning
confidence: 99%
“…Direct experimental evidence for the utility of extracorporeal affinity adsorption for increasing the maximum tolerated dose (MTD) of the 90 Y-and 177 Lulabeled BR96 was recently reported. 82 Antibodies were radiolabeled with a trifunctional chelating agent 1033, which contains DOTA and biotin. While the MTDs for 177 Lu-1033-BR96 and 90 Y-1033-BR96 are close to 600 and 350 MBq/kg, respectively, extracorporeal affinity adsorption allowed for administration of 1200 MBq/kg 177 Lu-1033-BR96 and 525 MBq/kg of 90 Y-1033-BR96 without any noticeable increase in the toxicity.…”
mentioning
confidence: 99%
See 1 more Smart Citation